Hubungan Penguasaan Gaya Bahasa Perbandingan Terhadap Kemampuan Menulis Puisi Siswa Kelas VII SMP Dwi Tunggal Tanjung Morawa Tahun Pembelajaran 2016/2017 - Annisa, Annisa (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
The purpose of this study is to determine the relationship of mastery of language style comparisonto the students' ability in writing poetry on the seventh grade students of SMP Dwi Tunggal Tanjung Morawa in the 2016/2017 academic year. The hypothesis of this study is the mastery of the comparison language style associated with poetry writing skills. The type of this research is quantitative descriptions using correlational approach. The sample of the research is 40 people and the sampling technique is random sampling because the population is 80 people consisting of two classes and the class is homogeneous. Data were collected with multiple choice tests, and performance tests. Data were analyzed by correlation technique. Based on data analysis, there is a relationship of mastery of comparative language style to students' ability to write poetry class VII Dwi Tunggal Junior High School Tanjung Morawa year of learning 2016/2017. The students' ability to master the comparative language style gets an average score of 73.88, then students write poetry get an average score of 72.88. And based on calculations using the formula Product Moment correlation r found that the ability to master the style of language is associated significantly with the ability to write a poem with correlation coefficient 0.678 (strong correlation) (0.678> 0.312), so it is interpreted that the ability to master the style of language is significantly related to writing poetry .Keywords: relationship, mastery, comparative language style, writing poetry